2019
DOI: 10.1016/j.jctube.2019.100099
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care for patients evaluated for tuberculosis in the context of Xpert MTB/RIF scale-up

Abstract: RationaleMany high-burden countries are scaling-up Xpert MTB/RIF using a hub-and-spoke model. We evaluated the quality of care for patients undergoing TB evaluation at microscopy centers (spokes) linked to Xpert testing sites (hubs) in Uganda.ObjectivesTo characterize the extent to which patients were receiving care in accordance with international and national guidelines.MethodsWe conducted a prospective cohort study of all adults with presumptive pulmonary TB at 24 health centers linked to Xpert testing site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

7
1

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…This sampling strategy suggests that our results may be generalized to rural and periurban TB care across the country. Our ability to identify challenges at each level in the Xpert referral implementation process aligns with the patient cascade of TB diagnostic care in Uganda [11], which demonstrates significant of pre-treatment loss to follow-up within this context. Our approach in understanding operational challenges to Xpert hub-and-spoke implementation may inform the development of targeted strategies to address these challenges while improving patient outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…This sampling strategy suggests that our results may be generalized to rural and periurban TB care across the country. Our ability to identify challenges at each level in the Xpert referral implementation process aligns with the patient cascade of TB diagnostic care in Uganda [11], which demonstrates significant of pre-treatment loss to follow-up within this context. Our approach in understanding operational challenges to Xpert hub-and-spoke implementation may inform the development of targeted strategies to address these challenges while improving patient outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…The number of health centers participating spanned 15 districts of Uganda, allowing us to feel secure in making generalizations about rural and peri-urban TB care across the country. Our ability to identify challenges at each level in the Xpert referral implementation process aligns these insights with the patient cascade of TB diagnostic care in Uganda [13], which demonstrates significance of pretreatment loss to follow-up within this context. Our approach in understanding operational challenges to Xpert hub-and-spoke implementation may inform the development of targeted strategies to address these challenges while improving patient outcomes.…”
Section: Field Notesmentioning
confidence: 86%
“…We found that willingness to return to the clinic increases proportionally with incentive amount, such that 25% of participants would return for an incentive of 500 USh, and 100% would return for 25,000 USh. If, as our WTA experiment found, the provision of a modest cash incentive of 5,000 USh could motivate up to 70% of patients who otherwise would not return to clinic to complete their diagnostic evaluation, completion of recommended testing in this context could be increased from a baseline of 56% (26) to over 80%. This change would substantially reduce patient attrition in the TB cascade of care.…”
Section: Discussionmentioning
confidence: 96%
“…We included community health centers if they used standard (multi-day) sputum smear microscopy and/or GeneXpert MTB/RIF (Cepheid, Sunnyvale USA) testing as the primary method of TB diagnosis. We excluded health centers that demonstrated low volume of TB testing and diagnosis: 1) performing sputum based TB diagnostic evaluation on < 150 patients per year, or 2) diagnosing < 15 smear positive TB cases per year (26).…”
Section: Study Setting and Populationmentioning
confidence: 99%